Factors Related to the Differential Development of Inter-Professional Collaboration Abilities in Medicine and Nursing Students - Berduzco-Torres, Nancy; Choquenaira-Callañaupa, Begonia; Medina, Pamela; Chihuantito-Abal, Luis A.; Caballero, Sdenka; Gallegos, Edo; San-Martín, Montserrat; Delgado Bolton, Roberto C.; Vivanco, Luis (Frontiers in Psychology, 2020)
Context: For physicians and nurses, teamwork involves a set of communication and social skills, and specific training in interdisciplinary work in order to be able to work together cooperatively, sharing responsibilities, solving problems, and taking decisions to carry out actions centred on patients’ care. Recent studies demonstrate that in the absence of targeted interdisciplinary educational programs, the development of teamwork abilities is sensitive to the influence of the dominant work environment. The purpose of this study was to characterize the role that environmental and individual factors play in the development of teamwork in environments with a dominant hierarchical work model. Methods: Questionnaires were distributed to 1,880 undergraduate students (980 medicine students and 900 nursing students) from three universities of Cusco city (Peru). The Jefferson Scale of Attitudes towards Physician-Nurse Collaboration was used as the main variable. Jefferson Scales of Empathy and Lifelong Learning, the Social and Emotional Loneliness Scale for Adults, the Scale of Life Satisfaction, sex, discipline, age and academic semester, were used as explanatory variables. After calculating internal reliability and normality of the main measures, descriptive, comparative and correlation analyses were performed to determine variables influencing the teamwork’s score. Results: A total of 1,518 (81%) surveys were returned fully completed. Adequate reliability was confirmed in all instruments. In the sample, nursing students showed greater inter-professional collaborative abilities than medicine students (p<0.001). This attitudinal gap was higher in advanced semesters. A three-way ANOVA indicated differences in teamwork associated to discipline (p<0.001), sex (p<0.01) and university (p<0.001). However, main effects were associated only to discipline (ηp2=0.14). Teamwork showed an inverse correlation with loneliness (ρ=-0.28; p<0.001), and a positive correlation with empathy (ρ=+0.49; p<0.001), and lifelong learning (ρ=+0.48; p<0.001). Teamwork positively correlated with life satisfaction only in the medicine students group (ρ=+0.15; p<0.001). Conclusions: These findings bring new evidence to support the main effect that social environments, in the absence of targeted interdisciplinary educational programs, play in the development of teamwork.